1995
DOI: 10.2166/wst.1995.0517
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment considerations for dissolved air flotation: water type, coagulants and flocculation

Abstract: Pretreatment considerations of coagulant selection, flocculation time and flocculation mixing intensity were studied for two different water supply types, aquatic humic and non-aquatic humic waters of low turbidity. Alum, ferric salts, and various polyaluminium chlorides (PACs) with different chemical properties were all effective in dissolved air flotation (DAF) when used under favorable conditions of dosage, pH, and flocculation time. A stoichiometry was found for the aluminium coagulants between coagulant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…The type of coagulant and its dose will determine how weIl a particle destabilizes (most often a reduction in its negative charge), aithough complete charge neutralization is not necessary. Bunker, et al, (1995) found that an organic polymer benefited alurn, but no PACl's when tested. Edzwald, (1995) noted that water with high concentrations of NOM have no need for the addition of an organic polymer to increase its hydrophobicity, and therefore enhance its ability to attach to air bubbles.…”
Section: Pretreatment Effectsmentioning
confidence: 96%
See 3 more Smart Citations
“…The type of coagulant and its dose will determine how weIl a particle destabilizes (most often a reduction in its negative charge), aithough complete charge neutralization is not necessary. Bunker, et al, (1995) found that an organic polymer benefited alurn, but no PACl's when tested. Edzwald, (1995) noted that water with high concentrations of NOM have no need for the addition of an organic polymer to increase its hydrophobicity, and therefore enhance its ability to attach to air bubbles.…”
Section: Pretreatment Effectsmentioning
confidence: 96%
“…The typical range of velocity gradients for flocculation basins is 10 to 100 s-' with detention hmes of up to 20 minutes. Detentions tirnes when DAF is used as the clarification process can be as low as 5 minutes, (Valdade, et al, 1996;Bunker, et al, 1995). Polymers may be added at the same time as the coagulant to induce bndging to produce larger, aithough more m i l e floc.…”
Section: Solubiiity Of Aliuninum Hydroxidementioning
confidence: 99%
See 2 more Smart Citations
“…En effet, l'adsorption d'ions métalliques à la surface des particules colloïdales modifie l'électronégativité de ces suspensions et fait augmenter par conséquent les probabilités de collision entre les particules. Le résultat final est une agglomération en microflocs, ensuite en flocs plus volumineux facilement décantables (BUNKER et al, 1995). Les techniques séparatives à membranes sont des procédés physiques de séparation solide-liquide mettant en oeuvre des membranes permsélectives dont les diamètres de pores sont compris entre 0,1 et 10 µm et qui permettent donc la rétention des particules en suspension, des bactéries, et indirectement des colloïdes et de certains ions après fixation de ces derniers sur de plus grosses particules obtenues par complexation, précipitation ou floculation (BERLAND et JUERY, 2002;CHOO et al, 2004).…”
Section: Introductionunclassified